Tinjauan Yuridis Peristiwa Revenge Porn dalam Konteks Undang-Undang ITE atau Undang-Undang Tindak Pidana Kekerasan Seksual - Nurhasanah, Hikmah; Nabilla, Anissa; Adelita, Nabila Putri; Haryani, Diah Septi; A, Abraham; A, Alreindra; M, Mulyadi (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Revenge porn, the illegal and unauthorized distribution of private sexual content, is an increasingly worrying issue in today's digital era. The purpose of this article is to conduct a legal review of the phenomenon of revenge pornography, with a focus on the existing legal framework in Indonesia, in particular the Electronic Information Transactions (ITE) Law and the Sexual Violence Crimes Law. This article uses a legal approach and critical analysis to explore the challenges and obstacles in handling revenge pornography cases within the existing legal framework and how to protect victims and enforce the law more effectively. Consider possible improvements in your efforts.